Attitudes of Students: Adoption of Scientific Attitudes and Interest in Increasing Study - Murniati Murniati; Erika Erika (Schrödinger: Journal of Physics Education, 2023)
Purpose of the study: The purpose of this research is to see an overview of the scientific attitude possessed by students at SMPN 17 Ksota Jambi based on indicators of adoption of scientific attitudes and indicators of interest in increasing science study time. Methodology: This research is a quantitative study, namely researchers using survey methods with data collection techniques using questionnaires. Main Findings: The results of the 2 attitude indicators discussed in this study are indicators of the adoption of a scientific attitude by 62.5% of students in the good category. While the interest in increasing the time to study science by 66.4% of students is in the sufficient category. Novelty/Originality of this study: The novelty of this research is an indicator used to describe the attitudes of students at SMPN 17 Kota Jambi, namely indicators of the adoption of a scientific attitude and an interest in increasing the time to study science.